THE P21/M ↔ C2/M PHASE TRANSITION IN SYNTHETIC AMPHIBOLE NA NAMG MG5 SI8 O22 (OH)2: THERMODYNAMIC AND CRYSTAL-CHEMICAL EVALUATION - Cámara F.; Oberti R.; Iezzi G.; Della Ventura G. (My University, 2003)
The P21/mC2/m displacive phase transition in the synthetic end-member amphibole Na NaMg Mg5 Si8 O22 (OH)2 has been studied by monitoring changes in unit-cell parameters and the intensities of superlattice reflections at 25–400 C. This amphibole allows investigation of the effects of compositional variations at the A- and B-group sites upon the transition. Polynomial fitting of a 24 Landau potential to the evolution of the order parameter with T yielded a T c of 257 3 C, and Landau coefficients compatible with a second-order transition. Structure refinement of single-crystal data collected at 25, 140, 270 and 370 C allowed modelling of the structural changes as a function of T and symmetry. Crystal-chemical analysis suggests that differences in T c in cummingtonites and in the crystal of this work depend mainly upon the relations between the aggregate ionic radii of the B- and C-group cations.
Keywords: Amphibole; HT-XRD; Displacive phase transition; Synthesis